Genera of Tischeriidae (Lepidoptera): a review of the global fauna, with descriptions of new taxa - Stonis, Jonas R.; Diškus, Arūnas; Remeikis, Andrius; Orlovskytė, Svetlana; Solis, M. Alma; Paulavičiūtė, Brigita; Xu, Jiasheng; Dai, Xiaohua (Zootaxa, 2023)
For the first time, genera of leaf mining Tischeriidae of the global fauna are reviewed and four new genera are described: Coptotrichoides Diškus & Stonis, gen. nov., trophically associated with Sapindaceae from Central and South America; Rytietia Diškus, Xu & Dai, gen. nov., trophically associated with Annonaceae from East and South East Asia; Pafazaria Diškus & Stonis, gen. nov., trophically associated with Fabaceae and Malvaceae from East and South East Asia; and Gnathitischeria Diškus, gen. nov., trophically associated with Malvaceae and Asteraceae from Central America. In addition to the descriptions of new genera, all previously described genera (Coptotriche Walsingham, 1890; Dishkeya Stonis, 2020; Tischeria Zeller, 1839; Manitischeria Diškus & Stonis, 2021; Neotischeria Diškus & Stonis, 2021; Paratischeria Diškus & Stonis, 2017; and Astrotischeria Puplesis & Diškus, 2003) are characterized and a pictorial identification key for all 11 genera is provided. Morphological and biological characteristics of all genera are supplemented with some molecular data. We described 12 new species: South East Asian Coptotriche sapaensis Diškus & Stonis, sp. nov.; Central American Coptotrichoides sapindoidum Diškus & Stonis, sp. nov. and Tischeria neokristenseni Diškus & Stonis, sp. nov.; South East Asian Rytietia uncinata Diškus, Xu & Dai, sp. nov., East Asian R. chongyiensis Xu & Dai, sp. nov.; South East Asian Pafazaria capitata Diškus & Stonis, sp. nov. and P. faboidica Diškus & Stonis, sp. nov.; Central American Neotischeria antigua Diškus & Remeikis, sp. nov. and N. subantigua Diškus & Remeikis, sp. nov.; South American Astrotischeria incae Diškus & Stonis, sp. nov.; and Central American Gnathitischeria atitlani Diškus & Stonis, sp. nov. and G. arcana Diškus & Stonis, sp. nov. The taxonomic rank of the East Asian subspecies Tischeria decidua siorkionla Kozlov, 1986 is elevated to species rank: T. siorkionla Kozlov (stat. nov.). The male genitalia of holotypes, paratypes, lectotypes or paralectotypes, or non-type specimens of some little-known species are examined for the first time. We provide the first morphological documentation for the following: Tischeria ceanothi lectotype and paralectotype; T. immaculata (stat. restored) paratype; Coptotrichoides deliquescens (Meyrick) lectotype and paralectotype; lectotypes of Coptotriche aenea (Frey & Boll), Astrotischeria plagifera (Meyrick), A. helianthi (Frey & Boll), and A. ephaptis (Meyrick); Coptotriche berberella (De Prins) paratype; and the first photographic documentation of Tischeria lvoskyi Kozlov holotype. Some non-type specimens deposited at NHMUK, including a few previously neglected species, are also examined and documented, including the American Astrotischeria solidagonifoliella (Clemens) and A. omissa (Braun). Nine new combinations are provided: Coptotrichoides deliquescens (Meyrick, 1915), comb. nov.; C. singularis (Stonis & Diškus) comb. nov.; C. suprafasciata (Diškus & Stonis) comb. nov., C. serjaniphaga (Remeikis & Stonis) comb. nov.; C. braziliensis (Diškus & Stonis) comb. nov.; Pafazaria jingdongensis (Xu & Dai), comb. nov.; Neotischeria explosa (Braun) comb. nov.; N. pallidipennella (Braun) comb. nov.; and Astrotischeria heteroterae (Frey & Boll) comb. nov. The synonymization of Tischeria longeciliata Frey & Boll, 1878 with Astrotischeria helianthi (Frey & Boll, 1878) is confirmed. One new species group, the Tischeria ceanothi group, is established. We also report a new distribution record of T. dodonaea Stainton from the Caucasus, Armenia. Three tables and 569 figures of adult external morphology, male and female genitalia, leaf mines, and cladograms based on molecular characters are provided.